Cumulative Live Birth Rates According to Maternal Body Mass Index After First Ovarian Stimulation for in vitro Fertilization: A Single Center Analysis of 14,782 Patients - Xue, Xia; Shi, Wenhao; Zhou, Hanying; Tian, Li; Zhao, Zhenghao; Zhou, Dangxia; Shi, Juanzi (Frontiers in Endocrinology, 2020)
Objective: To investigate the cumulative live birth rates (CLBR) according to body mass index (BMI) in women undergoing first in vitro fertilization (IVF). Design: Retrospective cohort analysis. Setting: An IVF clinic in a public hospital. Patients: This is a retrospective study of 14782 patients undergoing first fresh IVF cycles with subsequently frozen embryo transfer during Jan 2014-Jan 2017 in our clinic. The follow-up continued for CLBR until Jan 2019. Patients with a BMI <18.5 kg/m2 were considered to be underweight and those with a BMI > 24 kg/m2 were considered to be overweight (Obese ≥28 kg/m2). Intervention(s): None. Main Outcome Measure: The primary outcome was cumulative live birth rate (CLBR). Result(s): This study illustrated the “inverted U shape” associations between body weight and IVF outcome (CLBR). The turning points were BMI 18.5 kg/m2, 30.4 kg/m2 founded by automatic search turning point in threshold analysis. The main finding of this retrospective data analysis is that the CLBR increased from underweight to reach a plateau (normal weight and overweight with BMI 18.5 kg/m2, 30.4 kg/m2) and then decrease in obese with the accumulation of BMI. Conclusion(s): The data suggested an “inverted U shape” association between BMI and cumulative live birth rate. In particular, the CLBR increases in underweight women, reaching a plateau in normal weight and overweight, and then decreases in obese patients.